Effects of high stocking density on the growth performance, intestinal health and bile salts composition of broiler chickens - Dong, Yuanyang; Zheng, Yuqi; Liu, Haoyu; Wang, Yaru; Cui, Jiaqing; Wu, Yuan; Yan, Lei; Miao, Zhiqiang; Han, Miaomiao; Huang, Chenxuan; Li, Peifeng; Su, Yuan; et al. (Frontiers in Microbiology, 2025)
IntroductionThe intestinal dysfunction plays an important role in the decreased growth performance of broiler chickens under high stocking density. Gut microbiota plays an important role in maintaining intestinal health. However, the modulation pathway of gut microbiota by regulating the intestinal barrier and histomorphology remains unknown.MethodsOne hundred and forty-four male Arbor Acres broilers (22-d-old) with similar weight were randomly assigned to two treatments: a high (HSD, 20 broilers/m2) or low stocking density treatment (LSD, 14 broilers/m2), with six replicates per treatment. The experimental period was 20 days, from 22 to 42 days of age.ResultsThe final body weight at 42 days of age was lower in the HSD group (P = 0.0013) and average daily feed intake (P = 0.016) and weight gain of broilers from 22 to 42 days decreased (P = 0.012). In the HSD group on day 42, villus height and the ratio of villus height to the crypt depth in the ileum decreased (P < 0.05); mRNA expression of tight junction proteins, occludin (P < 0.01) and ZO1 (P < 0.05), were downregulated; whereas IL-6, TNFα, and NFκB p65 (P < 0.05) and IL-1β (P < 0.01) were upregulated. The HSD treatment increased the relative abundance of Lactobacillus (P = 0.045) and decreased that of Alistipes (P = 0.031). Cecal concentrations of acetic (P < 0.05) and butyric acids (P < 0.05) decreased. Gut metabolites co-metabolized by the host and gut microbiota were altered in the HSD group, with decreases in glycerophospholipid and tryptophan metabolites negatively correlated with Lactobacillus (P < 0.05). The metabolite content of conjugated bile acids decreased and free bile acids increased (P < 0.05) with HSD. Bile salt hydrolase (BSH) was increased in the intestine of HSD-treated broilers (P < 0.01). The total cholic acid content of the HSD group was lower in the jejunum and ileum (P < 0.05) but higher in the cecum than in the LSD group (P < 0.01).ConclusionHSD caused dysbiosis of the intestinal microbiota such as increased Lactobacillus, along with enhanced BSH activity and excessive unabsorbed free bile acids. This resulted in ileal epithelial cells damage, inflammation, decreased growth performance of broilers under high stocking densities.